Factors associated with gestational weight gain in pregnant women in Rio de Janeiro, Brazil, 2008 - Ana Claudia Santos Amaral Fraga; Mariza Miranda Theme Filha (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
Inadequate weight gain during pregnancy is an important predictor of complications for the mother and infant. This cross-sectional study assessed factors associated with inadequate weight gain among women in the third trimester of pregnancy who received prenatal care under the Brazilian Unified National Health System (SUS) in the city of Rio de Janeiro, Brazil, from November 2007 to July 2008. A total of 1,079 pregnant women were interviewed, and adequacy of weight gain was obtained by calculating weight gain as recommended by the U.S. Institute of Medicine. Social, demographic, and obstetric factors were analyzed as independent variables. A multinomial logistic regression model was used, and pregnant women with weight gain below or above the recommended levels were compared to those with adequate weight gain. Low schooling was associated with insufficient weight gain, while excessive gain was observed in women with hypertension and pre-gestational underweight, overweight, and obesity. Nutritional assessment during prenatal care is essential, and interventions should target cases of inadequate weight gain in order to prevent complications for the mother and infant.